Quality Management Implementation of Pilgrimage Guidance Groups (KBIH) in Medan City Under Law No. 8/2019 on Guidance and Assistance for Hajj Pilgrims - Hamdan Sukri Harahap; Ansari Yamamah; Hafsah Hafsah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This article explores the organizational management practices of the Pilgrimage Guidance Groups (KBIH) in Medan, focusing on the implementation of Law Number 8 of 2019 for Guidance and Assistance for Hajj and Umrah Pilgrims. Using a descriptive approach, data was collected through observations, interviews, and document analyses to investigate quality management, service delivery, and influencing factors at KBIH Medan. The findings demonstrate robust quality management, ensuring high-quality services and adherence to legal provisions. Service implementation covers planning, organizing, executing, mentoring, providing services, and supervision. Supporting factors involve legal considerations, regulatory frameworks, and pilgrim protection, while hindering factors encompass resource constraints, weather challenges, and diplomatic complexities. In conclusion, KBIH Medan effectively implements Law Number 8 of 2019, ensuring service quality and overcoming challenges for future efficiency. The research provides a comprehensive overview of KBIH's organizational management, significantly contributing to successful Hajj and Umrah implementation in Medan. The analysis indicates that KBIH An-Nabawy aligns with the 2019 Law, achieving service quality and effective guidance. Continuous attention and improvement are emphasized for optimal service quality, maintaining a delicate balance between legal adherence and logistical efficiency